Alteration in AMPA receptor subunit expression and receptor binding among patients with addictive disorders: A systematic review of human postmortem studies - Fumihiko Ueno; Takefumi Suzuki; Shinichiro Nakajima; Sachio Matsushita; Masaru Mimura; Tomoyuki Miyazaki; Takuya Takahashi; Hiroyuki Uchida (Wiley, 2019)
Abstract Background and Objectives Altered trafficking of α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptors has been reported in postmortem studies and suggested the involvement of AMPA receptors in the pathophysiology underpinning addictive disorders. However, these findings seemed mixed. Methods A systematic literature search was conducted, using PubMed and Embase (last search, August 2018), to identify human postmortem studies that examined the expression of proteins and mRNA of AMPA receptor subunits in patients with addictive disorders in comparison with healthy controls. Results Twelve (18 studies) out of 954 articles were identified to be relevant. Eight studies included alcohol use disorders, and four studies included heroin/cocaine abusers. The most frequently investigated regions were the hippocampus (three studies), amygdala (three studies), and putamen (three studies). In summary, two out of the three studies showed an increase in the expression of AMPA receptors in the hippocampus, while the other study found no change. Two studies to examine the amygdala demonstrated either a decreased or no change in receptor expression or binding. Concerning putamen, two studies showed no significant change whereas an overexpression of receptors was observed in the other. Conclusions and Scientific Significance The hippocampus and amygdala may be pertinent to addictive disorders through their functions on learning and memory, whereas findings in other regions were inconsistent across the studies. Human postmortem studies are prone to degenerative changes after death. Moreover, only qualitative assessment was conducted because of the limited, heterogenous data. These limitations emphasize the need to investigate AMPA receptors in the living human brains.